2007
DOI: 10.1016/j.euje.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of right ventricular systolic dysfunction by using myocardial acceleration during isovolumic contraction in patients with mitral stenosis

Abstract: TDI-derived right ventricular IVA may be used as an adjunctive, reliable, noninvasive parameter for the early detection of right ventricular systolic dysfunction in patients with MS but without signs of systemic venous congestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
6
43
1
4
Order By: Relevance
“…It can detect even small changes in the contractile function and is well correlated with the invasive or noninvasive measures of LV dP/dt [13,17]. Therefore, IVA can be used as a valuable and easy parameter for the quantification of global systolic function in various cardiac diseases [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can detect even small changes in the contractile function and is well correlated with the invasive or noninvasive measures of LV dP/dt [13,17]. Therefore, IVA can be used as a valuable and easy parameter for the quantification of global systolic function in various cardiac diseases [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Tayyareci et al [26] investigated the IVA of right ventricle in prediction of the degree of MS and demonstrated that Sm, IVV and IVA of right ventricle significantly decreased in the patients with MS compared to the control group, however, they noted that only right ventricle and IVA can predict the degree of MS. Decreased IVA of LV was shown in MS patients in our study, although it was not associated with the degree of stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Данный показатель хорошо зарекомендовал себя в каче-стве прогностического при заболеваниях правых отделов сердца [17,19,20,21,22]. Кроме того, в отличие от остальных индексов, этот параметр менее зависит от постнагрузки, однако широкие диапазоны нормальных значений (1,4-3,0 см/сек), полученные разными авторами, не позволяют ис-пользовать его как скрининговый метод оценки глобальной систолической функции правого желудочка.…”
Section: оценка глобальной и региональной сократимости правого желудочкаunclassified
“…The importance of this issue can be seen in the observation, that a dysfunctional preoperative right ventricular function is associated with postoperative regurgitation, requirement of more blood transfusion, longer intensive care unit stays and hospital stays [1]. An early involvement of right ventricular function in mitral valve stenosis is shown by Tayyareci, who performed a study to detect early signs of right ventricular dysfunction in patients with MS [2]. He found some evidence for an early systolic dysfunction in patients without signs of systemic venous congestion.…”
Section: Introductionmentioning
confidence: 99%